Chiral supercritical fluid chromatography-mass spectrometry with liquid chromatography fractionation for the characterization of enantiomeric composition of fatty acid esters of hydroxy fatty acids - Kozlov, Oleksandr; Lísa, Miroslav; Riecan, Martin; Kuda, Ondrej (Analytica chimica acta, 2025)
BACKGROUND: Fatty acid esters of hydroxy fatty acids (FAHFAs) are a recently discovered class of endogenous bioactive lipids with promising therapeutic potential for diabetes and inflammation. They represent complex mixtures of different isomers whose biological functions are the subject of investigation. Highly selective methods are required to characterize the composition of enantiomers in biological samples composed of many isobars and regioisomers. We aimed to develop a method for characterizing the enantiomeric composition of FAHFAs in biological samples using supercritical fluid chromatography-mass spectrometry (SFC-MS). RESULTS: The influence of key chromatographic parameters, such as column chemistry, mobile phase composition, and gradient, on the separation efficiency of 21 commercially available FAHFA regioisomers without stated absolute configuration and 4 FAHFA enantiomers was assessed. The optimized SFC-MS method utilizes a chiral column based on a tris-(3-chloro-5-methylphenylcarbamate) derivative of amylose (Lux i-Amylose-3) and acetonitrile-methanol mobile phase modifier, enabling fast enantioseparation of most FAHFA racemic pairs in 5 min. However, the SFC separation of FAHFA regioisomers was less effective, limiting its applicability to complex biological samples. To address this, we propose an offline two-dimensional separation approach with reversed-phase liquid chromatography for isolating FAHFA regioisomers, followed by chiral SFC-MS analysis of fractions. The suitability of the method was demonstrated by characterizing the enantiomeric composition of FAHFA in white adipose tissue and rice samples. The chiral analysis revealed the presence of both R- and S-FAHFA isomers in the samples, with one enantiomer being predominant. SIGNIFICANCE: The developed approach represents a proof of concept for the use of SFC-MS with LC prefractionation for the characterization of FAHFA enantiomeric composition in complex biological samples, providing a valuable tool for future research on the biological roles of bioactive lipids in health and disease.
Keywords: mastné kyseliny; Hydroxy Acids; Chromatography, Supercritical Fluid; Lipids; Fatty Acids; zvířata; Animals; hmotnostní spektrometrie; FAHFA; myši; Offline two-dimensional chromatography; Mass Spectrometry; Chiral separation; stereoizomerie; Mice; Chromatography, Liquid; Supercritical fluid chromatography; superkritická fluidní chromatografie; estery; Isomers; Esters; chromatografie kapalinová; hydroxykyseliny; Stereoisomerism